'State of the art' or dismal science? The economic debate in South Africa since 1994. (February 2016) - Fryer, David
Both the loss of prestige caused to mainstream economics by the global financial crisis and the resurgence of heterodox economics have proved to be superficial. 'Where it counts' (in the teaching of economics, in the most important policy circles, and in the most prestigious journals) neoliberal economics has proven resilient to dissent. Political dissent at South Africa's self-imposed structural adjustment programme peaked in 2007 at the ANC's elective conference and has subsequently lost impetus. Heterodox economics, although providing a more compelling account of the post-apartheid period, has for the most part been unable to penetrate the neoliberal bubble. This state of affairs is partly due to power relations, but it is also a function of the kind of economics that is regarded in the profession as 'state of the art'.